Accessibility and the bus system : transforming the world - Tyler, Nick, 1954- (Thomas Telford, 2016)
'Accessibility and the Bus System' explores the role of the bus system in enabling cities to function sustainably and efficiently by providing the necessary resources to support growing populations. The book takes a comprehensive view of what buses can and cannot do, and how to maximise the bus system's positive contribution while minimising the negative impacts.